Cultural and biochemical characteristics and fatty acid composition of Pseudomonas diminuta and Pseudomonas vesiculare. - Kaltenbach, C M (1975)
The cultural characteristics, biochemical activity, and cellular fatty acid composition of Pseudomonas diminuta and Pseudomonas vesiculare provided means for differentiation of these closely related species. Broth cultures of P. diminuta showed turbid growth and a distinct surface pellicle after 24 h at 35 C. P. vesiculare had no pellicle, and only light, diffuse growth was observed. All strains of P. vesiculare oxidized maltose and hydrolyzed esculin to varying degrees; P. diminuta was negative in these tests. The cellular fatty acids of these two species were similar, except that P. diminuta possessed a C19 cyclopropane acid which was not detected in P. vesiculare.